2021
DOI: 10.1088/1755-1315/788/1/012050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotics and encapsulated probiotics on enteric methane emission and nutrient digestibility in vitro

Abstract: The objective of this study was to evaluate the effects of probiotics and encapsulated probiotics on enteric methane production and the in vitro nutrient digestibility in ruminants. The probiotics used were from the group of lactic acid bacteria (LAB). The experiments were conducted in three dietary treatments (control diet, probiotics addition, and encapsulated probiotics addition) and three replicates. Each replicate was performed at a different week. The experimental diets were incubated in the in vitro rum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Moreover, García et al [46] reported that the Lactobacillus pentosus strain LB-31 demonstrated antagonistic activity and antimicrobial susceptibility, as well as tolerance to bile salts, pH changes and hydrophobicity. Furthermore, Abdelbagi et al [47] reported that probiotic strains (encapsulated or not) in in vitro studies decreased methane production and increased the total gas production in relation to the control treatment.…”
Section: Effect Of Probiotics On In Vitro Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, García et al [46] reported that the Lactobacillus pentosus strain LB-31 demonstrated antagonistic activity and antimicrobial susceptibility, as well as tolerance to bile salts, pH changes and hydrophobicity. Furthermore, Abdelbagi et al [47] reported that probiotic strains (encapsulated or not) in in vitro studies decreased methane production and increased the total gas production in relation to the control treatment.…”
Section: Effect Of Probiotics On In Vitro Resultsmentioning
confidence: 99%
“…This review article has 195 references: 192 articles published in peer-reviewed scientific journals, two chapters of scientific books from prestigious publishers and a reference from an international organization. For the effect of probiotics in in vitro studies, 20 references were used [30,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54], which demonstrate the desirable probiotic characteristics of bacterial isolates for survival in the gastrointestinal tract, the production of metabolites such as bacteriocin and its antagonistic effect on pathogens. It is necessary to replicate the in vitro and in vivo results, as well as to find the specific mode of action (biochemical reactions) of each proposed probiotic candidate in the animal host.…”
Section: Methodology Search Historymentioning
confidence: 99%
“…Nevertheless, an approach that is progressive, such as probiotics, involving methane measurements and mitigation strategies with an emphasis more on the biological reduction of methane emissions that occur due to direct-fed microbes, could be considered as a methane mitigation approach towards sustainability [85][86][87]. Researchers have developed numerous nutritional technologies to minimize CH 4 production, including direct inhibition techniques [88], feeding ruminants with additives [89], propionate enhancers [90], methane oxidizers [91], probiotics [92], defaunation [93], and manipulation of ruminant diets and hormones [84,94]. The study conducted by Abdelbagi et al [92] aimed to evaluate the impact of probiotics and encapsulated probiotics on enteric methane production and in vitro nutrient digestibility in ruminants.…”
Section: Mitigation Measures Of Methanementioning
confidence: 99%
“…Researchers have developed numerous nutritional technologies to minimize CH 4 production, including direct inhibition techniques [88], feeding ruminants with additives [89], propionate enhancers [90], methane oxidizers [91], probiotics [92], defaunation [93], and manipulation of ruminant diets and hormones [84,94]. The study conducted by Abdelbagi et al [92] aimed to evaluate the impact of probiotics and encapsulated probiotics on enteric methane production and in vitro nutrient digestibility in ruminants. The probiotics utilized were from the group of lactic acid bacteria.…”
Section: Mitigation Measures Of Methanementioning
confidence: 99%
“…Так, результаты in vitro у жвачных животных показали, что обычные и инкапсулированные пробиотики из группы молочнокислых бактерий снижали выработку метана соответственно на 6,1 и 33,1 % по сравнению с контролем. При этом авторы отмечали увеличение общего газообразования на 15,7 и 23,3 % при использовании тех же пробиотиков (71). В работе G. Guo и соавт.…”
unclassified